MEASURING THE COMPLEXITY IN THE PERUVIAN FINANCIAL MARKET - Rodriguez Carranza, Alexis (2015)
Information on the complexity of a phenomenon, may be obtained by measuring their levels of libertad.Asimismo that phenomenon paths converge to an attractor set, the degrees of freedom of the system, are the degrees of freedom of atractor. In this article we study the presence of an attractor for the dynamic set in the nancial market and estimate its dimension. They will be used the ideas of reconstruction of attractors using delay coordinates Takes and applications are centeredin the peruvian nancial market.